Resiliência moral de enfermeiros/as de um serviço de hemato-oncologia - Barbosa, Mariane da Silva (2023)
Introduction: Nurses working on oncology are daily confronted with suffering and uncertainties in their work environment. This leads these professionals to feel isolated and powerless in the face of challenges, which may require them to adopt an attitude of moral resilience. Moral resilience refers to the capacity to deal with crisis situations, particularly those related to moral principles, and to sustain or restore their integrity in response to moral complexity, confusion, distress, or setbacks. Objectives: To analyze the moral resilience of nurses in a hematology-oncology service in the face of ethical conflicts, and to describe the moral resilience strategies used by nurses in a hematology-oncology service when dealing with ethical conflicts. Method: This qualitative, exploratory-descriptive research was conducted in a public hospital institution in Rio Grande do Sul, specifically with hematology-oncology nurses. Data collection took place from January to May 2023, through semi-structured interviews conducted by the study's author. Discursive textual analysis was used. Ethical research considerations were respected. Results: Fourteen nurses participated in the study. The research results were presented in the form of two articles, the first being "MORAL RESILIENCE OF HEMATO-ONCOLOGY NURSES," which involved the intersection of the nurse's personal and professional roles, nurses' understanding of the limits of their ethical performance, and the impacts of moral resilience; and the second, "STRATEGIES FOR DEVELOPING MORAL RESILIENCE – VOICES OF HEMATO-ONCOLOGY NURSES," which considered strategies at the personal/self-awareness level and strategies for patient care. Conclusion: For nurses working in hematology-oncology, although moral resilience is a process of solitary readaptation and reconstruction, it is in the collective that these professionals find and unite their strengths. Developing moral resilience strategies is related to what these professionals believe to be relevant, considering not only the patient but also themselves. It is understood that further research should be developed on moral resilience with a focus on worker health.